Aggregation and Tunable Color Emission Behaviors of l‐Glutamine‐Derived Platinum(II) Bipyridine Complexes by Hydrogen‐Bonding, π–π Stacking and Metal–Metal Interactions. Issue 20 (12th March 2019) - Ai, Yeye; Li, Yongguang; Fu, Heidi Li‐Ki; Chan, Alan Kwun‐Wa; Yam, Vivian Wing‐Wah
Abstract: A nl ‐glutamine‐derived functional group was introduced to the bis(arylalkynyl)platinum(II) bipyridine complexes1 –4 . The emission could be switched between the 3 MLCT excited state and the triplet excimeric state through solvent or temperature changes, which is attributed to the formation and disruption of hydrogen‐bonding, π–π stacking, and metal–metal interactions. Different architectures with various morphologies, such as honeycomb nanostructures and nanospheres, were formed upon solvent variations, and these changes were accompanied by 1 H NMR and distinct emission changes. Additionally, yellow and red emissive metallogels were formed at room temperature due to the different aggregation behaviors introduced by the substituent groups on bipyridine. The thermoresponsive metallogel showed emission behavior with tunable colors by controlling the temperature. The negative Gibbs free‐energy change (Δ G ) and the large association constant for excimer formation have suggested that the molecules undergo aggregation through hydrogen‐bonding, π–π, and metal–metal interactions, resulting in triplet excimeric emission. Abstract : A series of bis(arylalkynyl) platinum(II) complexes withl ‐glutamine‐derived functional group was investigated. These complexes show various spectroscopic properties and aggregation behaviors. The emission could be switched between the 3 MLCT excited state and the triplet excimeric state through different solvents or temperatures; the changes were attributed to the formation and disruption of hydrogen‐bonding, π–π stacking and metal–metal interactions. The formed thermoresponsive metallogel showed emission behavior with tunable colors by controlling the temperature. The negative Gibbs free‐energy change (Δ G ) and the large association constant for excimer formation suggest that the molecules undergo aggregation through hydrogen‐bonding, π–π stacking and metal–metal interactions, resulting in triplet excimeric emission.